2018
DOI: 10.31228/osf.io/nc2z9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexism, Sexual Violence, Sexuality, and the Schooling of Girls in Africa: A Case Study from Lusaka Province, Zambia

Abstract: 23 Texas Journal of Women and the Law 37 (2013)While the education of girls is central to development in Africa, persisting obstacles have prevented the full implementation of this goal. African countries have made significant progress in expanding girls' participation in schooling, yet many girls remain unable to access and benefit from a quality education on an equal basis with boys. This study, involving interviews of 105 schoolgirls in and around Lusaka, Zambia in May 2012, describes and discusses the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…This scenario concurs with the study conducted by Bowman and Brundige (2013) in Lusaka, Zambia, which showed that the teacher beat the student after she refused to accept his proposal. They fear reporting the incidents of sexual harassment, fearing nothing would be done about it, and they would blame for what happened, and teachers would retaliate against them.…”
Section: Results: Gbv and Discrimination Against Girls Within Schoolssupporting
confidence: 91%
“…This scenario concurs with the study conducted by Bowman and Brundige (2013) in Lusaka, Zambia, which showed that the teacher beat the student after she refused to accept his proposal. They fear reporting the incidents of sexual harassment, fearing nothing would be done about it, and they would blame for what happened, and teachers would retaliate against them.…”
Section: Results: Gbv and Discrimination Against Girls Within Schoolssupporting
confidence: 91%
“…Instead, many of the policies endorsed sexual harassment myths that doubt and blame victims (Exposito et al, 2014;Hardt et al, 2022;Kara & Toygar, 2019;Lonsway et al, 2008). The findings support previous research from the sampled countries that show deeply rooted cultural norms that normalize sexual harassment and violence (Bowman & Brundige, 2013;Chireshe & Chireshe, 2009;Duma et al, 2016;Kampyongo et al, 2017;Kebirungi, 2021;Links, 2012;Machisa & van Dorp, 2012;Muasya, 2014;Newman et al, 2011;Nyaga, 2020;Wangusi et al, 2018;Wamoyi et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have identified sexual harassment as a problem at the University of Zambia, with perceptions of its severity differing by gender (Kampyongo et al, 2017;Menon et al, 2009Menon et al, , 2014. Bowman and Brundige (2013) report that sexual harassment and gendered norms of sexism and sexualization were rife in primary schools in Lusaka. Studies on secondary and postsecondary institutions in Zimbabwe also found sexual harassment is common, gendered, and under-reported citing cultural barriers (Chireshe & Chireshe, 2009;Mapuranga et al, 2015;Mlambo, 2014;Shumba & Matina, 2002).…”
Section: Anti-sexual Harassment Policy Guidelinesmentioning
confidence: 99%
“…Issues around consent in the Global North seem to differ to issues around consent in SSA. Sexual violence is prevalent globally; however, certain localities in the Global South report higher rates of sexual violence compared with the rest of the world (Bowman & Brundige, 2013), especially sexual violence involving issues of consent. Indeed, sociocultural contexts have nuanced variations of what constitutes consent.…”
Section: Stealthfully Violatedmentioning
confidence: 99%
“…Despite the first reported case of stealthing occurring in a more gender-equal nation, gender and sexual violence is a global problem and is particularly rife in SSA countries, where intergenerational and transactional sex, in addition to patriarchal power, further limits women's sexual autonomy and agency. For instance, Bowman and Brundige (2013) report that in Zambia young girls are constantly exposed to sexual violence from an early age, with prevalence rates reported at 15% to 40%. This high prevalence exists despite the placement of age of consent laws that are meant to protect girls at vulnerable ages (Harrison et al, 2017).…”
Section: What Is Stealthing?mentioning
confidence: 99%